Medical history of nocturnal enuresis during school age is an independent risk factor for nocturia in adults: The Nagahama study. Issue 1 (29th October 2020) - Negoro, Hiromitsu; Fukunaga, Arinobu; Setoh, Kazuya; Kawaguchi, Takahisa; Funada, Satoshi; Yoshino, Takayuki; Tabara, Yasuharu; Yoshimura, Koji; Kanematsu, Akihiro; Nishiyama, Hiroyuki; Matsuda, Fumihiko; Ogawa, Osamu; et al.
Abstract: Aim: To evaluate the relationship between nocturia and medical history of nocturnal enuresis: two conditions where diurnal urination rhythm is disturbed. Methods: The Nagahama study is a longitudinal population‐based health survey involving people aged 30–75 years in Nagahama city, Japan. Our analysis included 5, 402 participants who completed enuresis and International Prostate Symptom Score questionnaires. Associations between nocturnal enuresis and nocturia were evaluated cross‐sectionally and longitudinally with three models: (1) univariate analysis; (2) adjusted for basic characteristics (e.g., age, sex, body mass index, activity, alcohol, and smoking); and (3) adjusted for basic and clinical variables (e.g., hyperglycemia, hyperlipidemia, hypertension, renal insufficiency, insomnia, obstructive sleep apnea, and mental health). Results: In total, 1, 613 participants (29.9%) had a medical history of enuresis. The mean night‐time frequency was 0.73 at baseline and 0.85 at the 5‐year follow‐up. The cross‐sectional analysis showed participants with a medical history of enuresis had night‐time frequency more often than those without this history (0.84 vs. 0.68, p < .0001). Significant differences were observed in Models 2 ( p < .0001) and 3 ( p < .0001). The longitudinal analysis showed nocturia progression was significantly related to a history of enuresis, with odds ratios of 1.32 ( p < .0001) in Model 1, 1.21 ( p < .01) in Model 2, and 1.22 ( p < .01) in Model 3. Conclusions: Medical history of enuresis during school age was significantly related to nocturia in adulthood in the cross‐sectional analysis, and to progression to nocturia in the longitudinal analysis. These two conditions may possess a common causative association.